2010
DOI: 10.3920/bm2009.0036
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics lower plasma glucose in the high-fat fed C57BL/6J mouse

Abstract: Today, the gut microbiota is considered a key organ in host nutritional metabolism and recent data have suggested that alterations in gut microbiota contribute to the development of type 2 diabetes and obesity. Accordingly, a whole range of beneficial effects relating to inflammation and gut health have been observed following administration of probiotics to both humans and different animal models. The objective of this study was to evaluate the metabolic effects of an oral probiotic supplement, Lactobacillus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 26 publications
3
77
2
Order By: Relevance
“…[6][7][8][9] In particular, Lactobacillus plantarum exhibits various biological effects including antitumour, anticoagulant, antiviral, immune modulatory and anti-inflammatory, antidiabetic and antioxidant or free radical scavenging activity. [10][11][12][13] We reported that L. plantarum L67 isolated from infant faeces has a high survival rate at low pH values. The aim of this study was to determine whether a protein isolated from L. plantarum L67 induces programmed cell death in HT-29 cells.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] In particular, Lactobacillus plantarum exhibits various biological effects including antitumour, anticoagulant, antiviral, immune modulatory and anti-inflammatory, antidiabetic and antioxidant or free radical scavenging activity. [10][11][12][13] We reported that L. plantarum L67 isolated from infant faeces has a high survival rate at low pH values. The aim of this study was to determine whether a protein isolated from L. plantarum L67 induces programmed cell death in HT-29 cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to our genetically modified EcN, a number of unmodified probiotic bacteria also show antiobesity effects in mice (69)(70)(71)(72)(73). One clear advantage of using genetically modified gut microbiota rather than wild-type probiotics is the ability to choose both an appropriate carrier bacteria that can colonize the gut of the diseased individual and an appropriate therapeutic compound, whereas most probiotic bacteria are poor colonizers and the actual bioactive metabolites that confer their benefit poorly characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Andersson et al [10] reported the protective effects of a strain of Lactobacillus plantarum on obesity and early diabetes in, to highfat diet (HFD) fed C57BL/6J mice fed a high-fat diet for 20 weeks. Despite L. plantarum decreasing the plasma glucose level in a highfat diet fed mice, the energy intake, body fat content and plasma cholesterol were not different compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lactobacillus plantarum and Lactobacillus gasseri may exert a beneficial effect on the onset of diet-induced obesity by reducing the cell size of white adipose tissues [8,9]. Andersson et al [10] indicate that Lactobacillus plantarum DSM 15313 has anti-diabetic properties in the context of a high-fat diet.…”
Section: Introductionmentioning
confidence: 99%